APHORISMS AS AN OBJECT OF LINGUISTIC RESEARCH (Journal of Universal Science Research, 2023)
This paper deals with the cognitive study of the conceptual field of the English language aphorism. The methodology of the cognitive analysis of the textual concepts has been proposed and applied for the study of the means of verbalization of concept SCIENCE in English aphorisms.